2009
DOI: 10.1016/j.ijid.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of class 1 integrons among Pseudomonas aeruginosa isolates from patients in Zhenjiang, China

Abstract: Class 1 integrons were found to be widespread in P. aeruginosa isolated from clinical samples in the Zhenjiang area of China. The antibiotic resistance rates in class 1 integron-positive strains of P. aeruginosa were noticeably higher than those in class 1 integron-negative strains. PFGE showed that particular clones were circulating among patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 23 publications
10
41
2
Order By: Relevance
“…The reported percentages were higher compared to our study, which can be all due to the differences among geographical regions and the bacteria strains. The antibiotic resistance rates in class 1 integron-positive strains of P. aeruginosa were noticeably higher than those in class 1 integron-negative strains, which were in concordance with another study performed in China (11). While all isolated P. aeruginosa, resistant to cefepime, have had class 1 integron gene, in this study, the integrons were significantly associated with resistance to ofloxacin ( Table 1 and Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The reported percentages were higher compared to our study, which can be all due to the differences among geographical regions and the bacteria strains. The antibiotic resistance rates in class 1 integron-positive strains of P. aeruginosa were noticeably higher than those in class 1 integron-negative strains, which were in concordance with another study performed in China (11). While all isolated P. aeruginosa, resistant to cefepime, have had class 1 integron gene, in this study, the integrons were significantly associated with resistance to ofloxacin ( Table 1 and Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…This is not surprising, since many antibiotic resistance gene cassettes encoding resistance to a wide range of antibiotics have been reported previously. Thus, the intensification of resistance in isolated strains in different places showed the expansion of integrons in Gram negative bacteria (11,13,(19)(20)(21). Furthermore, the presence of integrons among different classes of antibiotics can cause serious problems in the distribution of this resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Rajat M et al in India reported that the level of resistance to ciprofloxacin, tobramycin, levofloxacin, gentamicin, and imipenem were 49%, 68%, 25%, 63%, and 14%, respectively (23). Another study carried out by Jioaguo Chen et al (24) in China demonstrated that the highest level of resistance was to cefoxitin (90%), ceftriaxone (88.7%), cotrimoxazole (84.5%), and piperacillin (69%), and the lowest level of resistance was to tobramycin (35.2%), amikacin (31%), ceftazidime, and imipenem (29.6%). It was also outlined by Bing et al that Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 98%
“…While 5' conserved region of class 1 integron includes class 1 integrase gene encoding a site-specific integrase (intI) and recombination site, 3' conserved region includes sulI and qacEΔ1 genes [18]. Class 1 integrons have been reported in P. aeruginosa isolates [8,[19][20][21][22][23][24][25][26][27]. Organization of class 2 integrons is similar to the class 1 integrons and they are inserted in the Tn7 transposons family.…”
Section: Introductionmentioning
confidence: 99%